Pengamalan Nilai-Nilai Toleransi Siswa SMA Negeri 3 Palangka Raya sebagai Bentuk Moderasi Beragama - Muhammad Azmi (ISLAMIKA, 2022)
This paper discusses the tolerance of SMA Negeri 3 Palangka Raya students. With differences in religion, ethnicity, and culture in the school environment, tolerance is needed so that there is no friction, but with tolerance, harmony will be realized in the school environment. By using field research (field research) with the methods used in collecting data by interview, observation and documentation methods, and qualitative descriptive data analysis, it was found that students at SMA Negeri 3 Palangka Raya, already have a high tolerance attitude. Tolerance at SMA Negeri 3 Palangka Raya has been carried out by students very well by always respecting religions that are different from one another, not insulting and disturbing the worship of other religions.